Morfologi Dasar Laut Dote (Laut Halmahera) Kabupaten Halmahera Tengah - Erik Febriarta; Septian Vienastra; Nurul Khakhim; Ajeng Larasati (LaGeografia, 2022)
Dote Village is located in Central Halmahera Regency with hilly morphology in the north and the coast bordering the Dote Sea (Halmahera Sea) in the south. The main transportation access in Dote Village is sea transportation. The condition of the Dote Sea waters which is busy with local transportation activities between villages requires updating data as basic information on the condition of the seabed depth (bathymetry). Seabed depth data can be obtained from bathymetric measurements and tidal analysis as a correction for bathymetric measurements. The morphological conditions of the seabed can provide information on the topographic characteristics of the seabed. Based on these conditions, the purpose of this research is to map the depth of the seabed (bathymetry) in the Dote Sea of Halmahera. The method used is direct measurement with echosunder. Then corrected with secondary data in the form of tidal condition data. Analysis of the data used is the value of the sea depth measured by echosounder compared to the mean sea level (MSL) (calculation of tides). Then mapping the morphology of the seabed using the slope method. The data used is the value of the depth of the sea (bathymetry) which is converted into the value of the slope with the analysis of the slope of the horton slope. Based on the measurement results, it is known that the bathymetry shows that the regional morphological conditions of the seabed slopes of the Halmahera Sea Dote are sloping.AbstrakDesa Dote berada di Kabupeten Halmahera Tengah dengan morfologi perbukitan di bagian utara dan pesisir yang berbatasan dengan Laut Dote (Laut Halmahera) di bagian selatan. Akses transportasi utama di Desa Dote adalah transportasi laut. Kondisi perairan Laut Dote yang ramai dengan kegiatan transpotasi lokal antar desa memerlukan pembaharuan data sebagai informasi dasar kondisi kedalaman dasar laut (batimetri). Data kedalaman dasar laut dapat diperoleh dari pengukuran batimetri dan analisis pasang surut sebagai koreksi pengukuran batimetri. Kondisi morofologi dasar laut dapat memberikan informasi karakteristik topografi dasar laut. Berdasarkan kondisi tersebut maka tujuan dari penelitian ini adalah pemetaan kedalaman dasar laut (batimetri) di Perairan Dote Laut Halmahera. Metode yang digunakan adalah pengukuran langsung dengan alat perum gema (echosunder). Kemudian dikoreksi dengan data sekunder berupa data kondisi pasang surut. Analisis data yang digunakan adalah nilai kedalaman laut hasil pengkuran dengan echosounder dibandingkan dengan nilai tinggi muka laut rata-rata atau mean sea level (MSL) (perhitungan pasang surut). Kemudian pemetaan morfologi dasar laut menggunakan metode kemiringan lereng. Data yang digunakan adalah nilai kedalaman laut (batimetri) yang dikonversi menjadi nilai kemiringan lereng dengan analisis kemiringan lereng horton. Berdasarkan hasil pengukuran diketahui batimetri diketahui bahwa kondisi morfologi regional lereng dasar laut Dote Laut Halmahera termasuk miring.